Climate extreme indices and its implication on crop production: The case of Mana district, Jimma Zone, Southwest Ethiopia - Biyeshi Ayansa Abdissa; Dessalegn Obsi Gemeda (Environmental and Sustainability Indicators)
Climate change is manifesting globally, with its effect on agricultural productivity becoming more apparent. There is no doubt that climate change is already affecting the economic development of developing countries. This research utilizes 40 years of historical climate data (1981–2021) to analyze temperature and rainfall trends and extreme climate indices in Mana district of Jimma zone in south-western Ethiopia. The significance level of temperature and rainfall trends and climate extreme indices were detected using Mann-Kendall's test statistics and the RClimDex, respectively. The study revealed that monthly maximum value of daily maximum temperature (TXx) and monthly minimum value of daily maximum temperature (TXn) experienced a statistically significant increasing trend (P < 0.05). The results also revealed that the mean maximum temperature ranged from 21 to 32 °C, while the average minimum temperature varied between 10.9 and 14.23 °C. Conversely, none of the rainfall trends and extreme indices demonstrated statistical significance. Results reveal that warm nights, warm days, and diurnal temperature ranges were experienced an increasing trend, which have tremendous impacts on crop production. Further studies should be conducted using climate data from multiple stations to measure the impacts of climate extremes on crop yield, which can give a tangible evidence for policymakers to design climate change adaptation and mitigation strategies.